Mereformasi Birokrasi dari Perspektif Sosio-Kultural: Inspirasi dari Kota Yogyakarta - Erisandi Arditama (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
The issue of administration and working management are not the only matters of bureaucracy complexity. However, in Yogyakarta it is also about the internalization of palace cultural interest into it. Hence, this article offers socio-cultural perspective as an alternative one in studying the city’s bureaucracy reformation and is hopefully useful for larger scope of Indonesian bureaucracy. By initiating the idea of deconstructive frame work, this study analyzes the strategies of Yogyakarta’s current mayor in term of braking down priyayi’s values in the city’s bureaucracy. At last, this study emphasizes that good leadership exemplary is the major key to actualize an open bureaucracy and serving mission at the same time.